2021
DOI: 10.1093/mnras/stab1965
|View full text |Cite
|
Sign up to set email alerts
|

uGMRT detection of cluster radio emission in low-mass Planck Sunyaev–Zel’dovich clusters

Abstract: Low-mass (M500 < 5 × 1014 M⊙) galaxy clusters have been largely unexplored in radio observations, because of the inadequate sensitivity of existing telescopes. However, the upgraded Giant Metrewave Radio Telescope (uGMRT) and the Low Frequency ARray (LoFAR), with unprecedented sensitivity at low frequencies, have paved the way to study less massive clusters more closely than before. We have started the first large-scale programme to systematically search for diffuse radio emission from low-mass galaxy c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…PSZ2 G080.16+57.65 (A2018) A radio relic in the E direction was discovered together with a candidate radio halo by van Weeren et al (2021) in the analysis of the LoTSS-DR1 cluster sample. More recently, Paul et al (2021) confirmed the presence of the two sources using uGMRT data at 300−500 MHz. In this paper, we confirm only the presence of the radio relic.…”
Section: Discussionmentioning
confidence: 83%
“…PSZ2 G080.16+57.65 (A2018) A radio relic in the E direction was discovered together with a candidate radio halo by van Weeren et al (2021) in the analysis of the LoTSS-DR1 cluster sample. More recently, Paul et al (2021) confirmed the presence of the two sources using uGMRT data at 300−500 MHz. In this paper, we confirm only the presence of the radio relic.…”
Section: Discussionmentioning
confidence: 83%
“…The sensitivity of the LOFAR data allows for easily detecting radio emission from groups and low-mass clusters: since the release of the LoTSS DR1 data, numerous discoveries of an extended radio structure in a lightweight galaxy system have been reported (see, e.g., Botteon et al [59,60], Hoang et al [61], Knowles et al [62], Paul et al [63]). Very recently, Paul et al [64] has shown that the uGMRT data gathered at 400 MHz are complementary to those from the LoTSS and are also a powerful tool to undercover diffuse radio emission in low-mass clusters; detections were made in systems that are characterised by masses around 2-3 times larger than the theoretical upper limit for galaxy groups modelled by Paul et al [21]. This is a strong hint that the uGMRT can easily handle observing group radio emission too-offering not only excellent comparison data, but also a possibility to bring studies on the group magnetism to a whole new level: for example, by using the combined uGMRT and LOFAR data to create high-resolution maps of the strength of the magnetic field within the studied system.…”
Section: The Character Of the Radio Emission From Galaxy Groups: Current Knowledge And Future Perspectivesmentioning
confidence: 98%
“…The sensitivity of the LOFAR data allows to easily detect radio emission from groups and low-mass clusters: since the release of the LoTSS DR1 data, numerous discoveries of an extended radio structure in a lightweight galaxy system have been reported (see eg. Botteon [59] has shown that the uGMRT data gathered at 400 MHz are complementary to those from the LoTSS and are also a powerful tool to undercover diffuse radio emission in low-mass clusters; detections were made in systems that are characterised by masses around 2-3 times larger, than the theoretical upper limit for galaxy groups modelled by Paul et al [57]. This is a strong hint that the uGMRT can easily handle observing group radio emission, too -offering not only excellent comparison data, but also a possibility to bring studies on the group magnetism to a whole new level: for example, by using the combined uGMRT and LOFAR data to create high-resolution maps of the strength of the magnetic field within the studied system.…”
Section: The Character Of the Radio Emission From Galaxy Groups: Curr...mentioning
confidence: 99%